P147 Origin of referrals seen by occupational physicians who report work related asthma. (December 2018) - Hoyle, JL; Carder, M; Money, A; Seed, M; Sen, D; Agius, RM; Van Tongeren, M
Abstract : Introduction and objectives: Regulations published by the Health and Safety Executive (HSE) UK advise health surveillance programmes for some workplaces. Little is known about the proportion of work related asthma cases diagnosed by the health surveillance route. This study aims to investigate the origin of referral to occupational physicians (OP'-s) who then report work related asthma. Methods: Incident cases of work related asthma reported to The Health and Occupation Research (THOR) network between 2006 and 2017 were extracted. For each case, OP'-s provide the diagnosis, age and gender, occupation, industry, suspected causal agent(s), and reason for referral. Data for occupational asthma cases from OP'-s was examined with reason for referral. Results: 135 of 137 asthma cases reported by OP'-s documented reason for referral, of which:- 71 were males (52%) and with an average age of 42.8 years (range 19–67 years). Reason for referral: 59 (44%) employer referral reason not specified, 23 (17%) routine health surveillance, 23 (17%) sickness absence, 17 (13%) self-referral, 8 (6%) research or HSE investigation, 3 (2%) assessment for early retirement, 1(<1%) medico-legal, 1(<1%) pre-placement. Conclusions: In over 2 out of 5 cases of work related asthma reported by OP'-s, the reason an employer referred the case remains unclear; however at least 1 in 6 cases of work related asthma were referred to occupational physicians based on health surveillance. The same number of cases was reported from health surveillance as sickness absence. Further interrogation as to why an employer refers a case may influence these figures thus they are likely to be a minimum estimate of cases found by health surveillance by OP's. It is not known how many subjects in total have undertaken health surveillance to find these cases.